Comparison of corrosion behavior on laser welded austenitic stainless steel. (2021) - Gnanarathinam, A.; Palanisamy, D.; Manikandan, N.; Devaraju, A.; Arulkirubakaran, D.
Abstract: Austenitic stainless steel is one among the most commonly adopted materials for various engineering applications such as nuclear reactors, internals of vessels and valve body due to exceptional characteristics. Welding is an important process in manufacturing which helps to join the material in an effective manner, especially with help of laser welding. Corrosion is a phenomenon which huge contribution on environmental destruction also influences the all the metallic materials. It is a common issue for all the manufacturing industries such as petroleum, aerospace and marine. This present investigation an endeavor has been taken to analyze the corrosion rate with different mediums such as ferric chloride, nitric acid and Oxalic acid. The rate of corrosion has been assessed by weight loss method. The outcome of this experimentation witnessed that the rate of corrosion is increased with respect to temperature and time. Increase in temperature makes considerable chemical reactions which consequences significantly on the rate of corrosion. A comparison has been done to corrosion behavior of laser beam welded 304L Stainless steel samples and results are presented. The composition existing in the selected material contributes for reducing the corrosion rate especially in acidic environments.